(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The Qajar dynasty (1789–1925) was a time of great change and difficulty for Iranian women. This was because of their early experiences with modernity, changing social structures, and traditional patriarchal norms. Women of this period managed various identities as daughters, wives, mothers, and, at times, as political figures in royal courts and aristocratic households. Religious and cultural norms restricted women’s public roles, yet women often leveraged their private lives as avenues to exert social and familial influence. Elite women, especially those in the royal harem, had a big impact on court politics, diplomacy, and cultural patronage. They did this by subtly influencing state policies and artistic expressions. In a society dominated by men, average women faced the burden of domestic work, severe gender segregation, and limited legal rights. The late Qajar era saw the beginning of socio-political change that would later pick up steam in the Pahlavi era, as evidenced by early feminist voices calling for women’s emancipation and literacy, reformist movements, and educational initiatives. The social standing, legal rights, cultural contributions, and developing political consciousness of Iranian women during the Qajar dynasty are all examined in this article, along with their varied experiences in the larger framework of Iran in the late 19th and early 20th centuries.